2020
DOI: 10.2147/ott.s244181
|View full text |Cite
|
Sign up to set email alerts
|

<p>LncRNA HCG11 Suppresses Cell Proliferation and Promotes Apoptosis via Sponging miR-224-3p in Non-Small-Cell Lung Cancer Cells</p>

Abstract: Introduction Studies have found that Lnc-HCG11 is an important regulator of cancer. However, the function of Lnc-HCG11 in NSCLC is not known. Therefore, this experimental design was based on Lnc-HCG11 to explore the pathogenesis of NSCLC. Methods RT-qPCR was used to detect the expression of Lnc-HCG11 and miR-224-3p in NSCLC. The effects of Lnc-HCG11 and miR-224-3p on proliferation and apoptosis of NSCLC cells were detected by CCK-8 assay, Edu assay and Annexin V-FITC/PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…1 Although surgery, radiotherapy, and chemotherapy have great progress, the 5-year survival rate of NSCLC patients is still less than 19% due to relapse and drug resistance, and the lack of sensitive and efficient early diagnostic markers. [2][3][4][5] Therefore, it is imperative to conduct an indepth research of the molecular mechanism of the occurrence and development of NSCLC, so as to provide a theoretical basis for diagnosis and therapy of NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…1 Although surgery, radiotherapy, and chemotherapy have great progress, the 5-year survival rate of NSCLC patients is still less than 19% due to relapse and drug resistance, and the lack of sensitive and efficient early diagnostic markers. [2][3][4][5] Therefore, it is imperative to conduct an indepth research of the molecular mechanism of the occurrence and development of NSCLC, so as to provide a theoretical basis for diagnosis and therapy of NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there was a correlation between the expression of miR-224-3p and Lnc-HCG11. Caspase-3 and c-caspase-3 expression levels were up-regulated by the overexpression of lnc-HCG11 (37). The HCG11/miR-1276/CTNNB1 axis controlled the occurrence and progression of GC.…”
Section: Discussionmentioning
confidence: 96%
“…Some studies have reported that HCG11 was high-expressed in gastric cancer and can accelerate proliferation and migration in gastric cancer [21]. Other research have found that HCG11 was low-expressed in non-small-cell lung cancer and blocked cell proliferation and accelerated apoptosis in non-small-cell lung cancer [22]. Moreover, it is also proved that abnormally expressed HCG11 is closely related to poor prognosis in breast cancer [11], but the speci c mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 99%